2006
DOI: 10.1093/nar/gkl562
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Dmc1-mediated DNA strand exchange by the human Rad54B protein

Abstract: The process of homologous recombination is indispensable for both meiotic and mitotic cell division, and is one of the major pathways for double-strand break (DSB) repair. The human Rad54B protein, which belongs to the SWI2/SNF2 protein family, plays a role in homologous recombination, and may function with the Dmc1 recombinase, a meiosisspecific Rad51 homolog. In the present study, we found that Rad54B enhanced the DNA strandexchange activity of Dmc1 by stabilizing the Dmc1-single-stranded DNA (ssDNA) complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 60 publications
1
21
0
Order By: Relevance
“…The stimulation of the complex formation between S100A11 and Rad54B is obviously time dependent, with the highest number of S100A11-Rad54B complexes after approx. 3 h. These kinetics are also similar to the temporal stimulation of the Dmc1 recombinase-mediated DNA strand exchange activity by Rad54B (Sarai et al, 2006). As reported, after transfer of S100A11 into the nucleus, an induction of the CDK inhibitor p21 WAF1/CIP1 is initiated (Sakaguchi et al, 2003).…”
Section: Discussionsupporting
confidence: 82%
“…The stimulation of the complex formation between S100A11 and Rad54B is obviously time dependent, with the highest number of S100A11-Rad54B complexes after approx. 3 h. These kinetics are also similar to the temporal stimulation of the Dmc1 recombinase-mediated DNA strand exchange activity by Rad54B (Sarai et al, 2006). As reported, after transfer of S100A11 into the nucleus, an induction of the CDK inhibitor p21 WAF1/CIP1 is initiated (Sakaguchi et al, 2003).…”
Section: Discussionsupporting
confidence: 82%
“…hRAD54B interacts with human RAD51 and DMC1, and enhances the D-loop formation of both proteins [64, 169, 170]. Further work is needed to understand the functional specification between hRAD54 and hRAD54B in vertebrates.…”
Section: Functions Of the Rad54 Paralogs Scrdh54 And Hrad54bmentioning
confidence: 99%
“…For RecA (Kowalczykowski et al 1994;Papavinasasundaram et al 1997;Voloshin et al 2001) and Rad51 (Sung et al 2003;Krogh and Symington 2004) a number of well-characterized factors have been described. For Dmc1, however, the detailed biochemical mechanisms of its accessory proteins are unknown (Chen et al 2004;Hayase et al 2004;Sehorn et al 2004;Petukhova et al 2005;Haruta et al 2006;Pezza et al 2006;Sarai et al 2006). Both genetics and biochemical studies have demonstrated the functional interaction between Dmc1 and Hop2/Mnd1 proteins.…”
Section: A Presynaptic and Synaptic Role For Hop2/mnd1 In Meiotic Recmentioning
confidence: 99%